fMRI neuroinformatics. - Nielsen, F.A.
Functional magnetic resonance imaging (fMRI) generates vast amounts of data. The handling, processing, and analysis of fMRI data would be inconceivable without computer-based methods. fMRI neuroinformatics is concerned with research, development, and operation of these methods. Reconstruction, rudimentary analysis, and visualization tools are implemented in software controlling modern MRI scanners. Research in advanced methods for analysis of subtle activation patterns, realistic physiological modeling, or integration of data from multiple subjects is the basis for a lively research field and has led to the development of a large number of tools.
Keywords: MRI scanners; Activation patterns; Computer-based methods; Data handling; Data processing; fMRI data analysis; fMRI neuroinformatics; Functional magnetic resonance imaging; Physiological modeling; Reconstruction tool; Rudimentary analysis; Software control; Visualization tool